Causes and Consequences of Cross-border Migration of Nepalese People to India - Kunwar, Laxman Singh (Patan Pragya, 2022)
Nepal and India share an open border as per the agreements of a bilateral treaty signed in 1950.According to the treaty, people of both countries can travel and work across the border and are to be treated at par with the native citizens. Due to its poor economic condition, Nepal has been supplying labour to India since Nepalese were recruited as ‘Gorkhas’ in the British Indian army after the Anglo-Nepal war of 1814-16. The 1991 and 2001 Censuses of Nepal recorded that absentee population from Nepal towards India constituted 89.2 and 79 per cent of the total migrants respectively, though this phenomenon has changed over the recent years. There has been increasing a trend of migration to Gulf countries, Asian Tiger States, American and European countries. This article is based on secondary data sources. People who are not that much skilled and have not enough resources are going to south East Asian countries, mainly to Malaysia, and Middle East. Nearly more than four-fifths of per cent absenteeism from Nepal remained in India. The similar socio-cultural, religious patterns, historical and geographical setting favor in participating on cross-border migration between two countries.